Impact of Strategy Implementation on Performance of Generic Strategy: Evidence from Thailand - Chaimankong, Mayookapan; Prasertsakul, Dissatat (The South East Asian Journal of Management, 2012)
The purpose of this paper is to examine the strategic orientation in terms of Miles and Snow typologies of the firms in emerging country and investigate their implications on performance. Unlike previous research, this paper focuses the importance of strategy implementation to the performance implications of Miles and Snow typology. Data was collected from 111 key informants from firms in Thailand’s chemical industry using probability sampling. The one-way Analysis of Variance (ANOVA) results showed that prospectors performed better than the other three strategic types, whereas reactors exhibited the lowest performance scores. While the success in strategy implementation is found to be a significant predictor of firm performance, the two-way Analysis of Variance (ANOVA) results revealed that the success in strategy implementation did not alter the relationship between Miles and Snow strategic type and a firm’s performance. This finding suggests that the relationship between Miles and Snow strategic type and a firm’s performance may be universal, regardless of the location where the study is conducted. However, additional studies in other contexts are required before the conclusion can be made whether the strategic type – performance relationship will be contingent on strategy implementation.